Patient perspectives of sickle cell disease care in emergency centres of South African Hospitals - Peerbhai, Nabeelah (Department of Pathology, 2025)
Introduction: Sickle Cell Disease (SCD) is an inherited, chronic blood disorder. Patients affected by SCD experience systemic, life-threatening complications that requires frequent emergency care. Western studies have reported poorer experiences by individuals with SCD when seeking emergency care compared to other chronic conditions. Aim: This study aimed to investigate the perceived experiences of adult patients with SCD who presented for care to the emergency centres of South African hospitals. Methods: A mixed methods approach was used to conduct this research. Participants were recruited from the Sickle Cell South Africa online support group and Groote Schuur Hospital in Cape Town. Surveys were completed by 51 participants and then analysed using both descriptive and comparative statistics. Open-ended interviews were conducted with eight of the participants, which were analysed using thematic analysis. Results: In the last five years, 47.5% of participants visited the emergency centres between two and five times, 29.4% attended more than five times and the remainder attended only once. Most respondents (45.1%) described their recent experience in the emergency centre as average, while 31.4% described their experience as good and 23.5% as poor. Exploring participant confidence levels identified 21.6% of participants felt very confident in the nurses treating them while more participants (33.3%) felt very confident in the doctor treating them. Five themes emerged from the data 1) Knowledge and understanding of SCD amongst healthcare professionals and patients, 2) Treatment in emergency centres, 3) Patient advocacy and support, 4) Emotional and psychological impact and 5) Access to healthcare and care coordination. Participants identified a lack of knowledge and understanding amongst HCPs relating to SCD, which they believe, contributed to delayed care, misunderstanding of the condition, disbelief in their symptoms and ignorance regarding their pain. Notably, participants expressed a higher confidence in doctors' understanding of SCD than nurses', highlighting the need for targeted education interventions. Participants further emphasized the importance of comprehending their own condition and being able to articulate the nature of SCD pain, which may or may not be visible. The treatment received in the emergency centre, such as the urgency of receiving medical care, the essential need for patient-centred pain management, challenges with the triage system and the positive influence of strong physician patient interactions, played a role in the type of experience they had. Self-advocacy and family/social support were important factors when receiving emergency care. Patients developed various coping mechanisms yet expressed the challenge of navigating pain symptoms, anxiety, fear, and uncertainty. Lastly, patients described transport and financial challenges when accessing healthcare services, as well as the need for coordinated healthcare services inclusive of genetic counselling. These results were consistent across both public and private facilities, with no statistically significant difference being noted between the two. Conclusion: Insight into patient experiences can actively involve patients in managing their health to ensure the patient's voice is heard. This research identified factors contributing to patient perceptions, the strengths of emergency care while suggesting potential solutions to better patient satisfaction.